Penetration of a glass-faced transparent elastomeric resin by a lead-antimony-cored bullet - Hazell, Paul J.; Edwards, Michael R.; Longstaff, H.; Erskine, J. (Elsevier, 2009)
The penetration of the lead antimony-cored 7.62 mm × 51 mm bullet into a glass- faced polyurethane elastomeric polymer resin has been studied. The resulting craters in the resin contained elongated bullet core material that had a significant amount of porosity. A simple linear viscoelastic model was applied to AUTODYN-2D to describe the behaviour of the resin and numerical results of the penetration mechanism and depth-of-penetration appeared to match experimental observations well. Analysis of the high speed photography and a numerical model of this bullet penetrating a viscoelastic polymer showed that during the initial stages of penetration, the projectile is essentially turned inside out. Furthermore, the shape of the cavity was defined by the elastic relaxation of the polymer that led to compression of the core material. A weight analysis of the penetrated materials showed that using a thicker tile of glass resulted in better ballistic performance.
Keywords: bullet impact; transparent armour; modelling; elastomeric resin